2009
DOI: 10.1080/14017430802506601
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after coronary artery bypass surgery. A 10-year follow-up study

Abstract: Younger age and preoperative employment were the most important predictors of successful return to work. Once returned after CABG, patients' staying at work was comparable with that in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 25 publications
0
33
1
2
Order By: Relevance
“…Younger age has been introduced as a predictor of RTW in several studies [12,17,[24][25][26][27][28][29]. However, in this study, despite a significant association between the younger age (especially under 60) and early return to work, in the univariate analysis, the association of age was not statistically significant in the suggested model of logistic regression analysis.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Younger age has been introduced as a predictor of RTW in several studies [12,17,[24][25][26][27][28][29]. However, in this study, despite a significant association between the younger age (especially under 60) and early return to work, in the univariate analysis, the association of age was not statistically significant in the suggested model of logistic regression analysis.…”
Section: Discussioncontrasting
confidence: 53%
“…However, in the present study the association of higher education was no longer significant in the suggested model of logistic regression. Being employed before the surgery was another RTW predictor [8,27] that could not be evaluated in this study since all the study cases were employed. However, duration of preoperative absence from work was inversely associated with the probability of early return to work, and directly associated with the time interval between the surgery and return to work (in days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En cuanto a las variables socioeconómicas la edad es un predictor potente y así aparece en la mayoría de los estudios publicados 17,[24][25][26][27] . El riesgo de tener una incapacidad permanente se incrementa de forma significativa a partir de los 50 años (80,3% en <50 años y 70,5% en> 50 años).…”
Section: Discussionunclassified
“…No obstante es menor que la publicada en estudios previos (243 días de media de duración de IT en el estudio de ) y claramente superior a la duración media de los países de nuestro entorno en los que mayoritariamente se reincorporan antes de los 6 meses 25,37 . Probablemente la descoordinación entre niveles asistenciales puede ser una causa importante responsable de esta prolongación de la I. T. En la mayoría de los casos es el médico de atención primaria quien da los partes de baja y en su momento el alta.…”
Section: Equipos De Valoración De Incapacidades De Inss (Evis)unclassified